Frameworked electrolytes: Ionic transport behavior and high mobility for solid state batteries - Sun, Jianguo; Yuan, Hao; Yang, Jing; Wang, Tuo; Gao, Yulin; Zhao, Qi; Liu, Ximeng; Wang, Haimei; Zhang, Yong‐Wei; Wang, John (InfoMat, 2024)
All solid‐state batteries (ASSBs) are the holy grails of rechargeable batteries, where extensive searches are ongoing in the pursuit of ideal solid‐state electrolytes. Nevertheless, there is still a long way off to the satisfactorily high (enough) ionic conductivity, long‐term stability and especially being able to form compatible interfaces with the solid electrodes. Herein, we have explored ionic transport behavior and high mobility in the sub‐nano pore networks in the framework structures. Macroscopically, the frameworked electrolyte behaves as a solid, and however in the (sub)‐nano scales, the very limited number of solvent molecules in confinement makes them completely different from that in liquid electrolyte. Differentiated from a liquid‐electrolyte counterpart, the interactions between the mobile ions and surrounding molecules are subject to dramatic changes, leading to a high ionic conductivity at room temperature with a low activation energy. Li+ ions in the sub‐nano cages of the network structure are highly mobile and diffuse rather independently, where the rate‐limiting step of ions crossing cages is driven by the local concentration gradient and the electrostatic interactions between Li+ ions. This new class of frameworked electrolytes (FEs) with both high ionic conductivity and desirable interface with solid electrodes are demonstrated to work with Li‐ion batteries, where the ASSB with LiFePO4 shows a highly stable electrochemical performance of over 450 cycles at 2°C at room temperature, with an almost negligible capacity fade of 0.03‰ each cycle. In addition, the FE shows outstanding flexibility and anti‐flammability, which are among the key requirements of large‐scale applications. A new class of frameworked electrolytes (FEs), where the “macroscopically solid” frameworks are purposely laden with 3D channels of high ionic mobility in sub‐nano‐scale in the extensive pore networks, giving rise to both high ionic conductivity and desirable interface with the electrode solids.